2004
DOI: 10.1179/174328904x19958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV light, electron beam and gamma irradiation on capillary flow of LLDPE and LLDPE filled with sericite–tridymite–cristobalite

Abstract: The rheological properties of linear low density polyethylene (LLDPE) were modified by irradiation in order to reduce or eliminate the unstable region (spurt) on the flow curve. Three different types of irradiation source (gamma ray, electron beam and UV light) were used to introduce the oxygencontaining groups into molecular chains of LLDPE, and consequently attain chain scission without any chemical additives resulting in smooth flow without any evidence of instability. This was proved by FTIR and contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The ESCA spectra of exposed polyolefin1 clearly reveals the generation of new peaks resulting from plasma oxidation, namely C2 at 286.5 eV due to CO groups (hydroxyl, ether, or epoxide), C3 at 288.0 eV due to CO or OCO (carbonyl or double ether), and C3 at 289.4 eV due to OCOH or OCOC. Honek et al11 have revealed that irradiation of polyolefin through electron beam and γ‐rays have essentially introduced oxygen‐containing groups into molecular chains of polyolefin, resulting in increasing adhesion with polar fillers. It has been reported that when the PBI surface has been modified by the exposure under an electron beam, the IR (ATR) spectroscopy revealed the generation of CO 2 H units at the site of the polymer backbone and the concurrent loss of fluorine groups (OCF 2 C(CF 3 )F) n OCF 2 CF 2 SO 3 H into the side chain, leading to significant increase in hydrophilic properties of the polymer 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESCA spectra of exposed polyolefin1 clearly reveals the generation of new peaks resulting from plasma oxidation, namely C2 at 286.5 eV due to CO groups (hydroxyl, ether, or epoxide), C3 at 288.0 eV due to CO or OCO (carbonyl or double ether), and C3 at 289.4 eV due to OCOH or OCOC. Honek et al11 have revealed that irradiation of polyolefin through electron beam and γ‐rays have essentially introduced oxygen‐containing groups into molecular chains of polyolefin, resulting in increasing adhesion with polar fillers. It has been reported that when the PBI surface has been modified by the exposure under an electron beam, the IR (ATR) spectroscopy revealed the generation of CO 2 H units at the site of the polymer backbone and the concurrent loss of fluorine groups (OCF 2 C(CF 3 )F) n OCF 2 CF 2 SO 3 H into the side chain, leading to significant increase in hydrophilic properties of the polymer 18.…”
Section: Discussionmentioning
confidence: 99%
“…Glow discharge under low‐pressure plasma is a popular technique, which results in better uniformity in the surface modification of the polymers 8–10. The present trend of research reveals that modification of polymers through high‐energy radiation could also be beneficial in the context of polymeric composite 11, 12. In this regard, the surface of PBI sheet is modified by high‐energy radiation for 6 h in the pool of a SLOWPOKE‐2 nuclear reactor, which produces a mixed field of thermal and epithermal neutrons, energetic electrons and protons, and γ‐rays, with a dose rate of 37 kGy/h12 and low‐pressure plasma using a 13.56 MHz RF Glow Discharge for 120 s at 100 W of power13 using nitrogen as process gas, to essentially increase the surface energy of the polymer, leading to substantial improvement of its adhesion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The recent understanding of modification of polymeric composites through high-energy radiation could also be beneficial in the context of a polymeric composite [14,15]. In this regard, the surface of a polybenzimidazole sheet is modified by low-pressure plasma using a 13.56 MHz RF glow discharge for 120 s at 100 W of power [16] using nitrogen as the process gas to essentially increase the surface energy of the polymer, leading to a substantial improvement of its adhesion characteristics.…”
Section: Introductionmentioning
confidence: 99%